Comparison between biodegradable polymers from cassava starch and glycerol as additives to biogas production - Cremonez, Paulo André (2016)
In this study, we compared cassava starch-based biodegradable polymers (PBMs) and glycerol (G) as additives used to increase biogas production from the co-digestion of swine wastewater (ARS). We chose to work with an inoculum comprising 40% (v/v) of the total volume of the reactor; this inoculum was obtained from a Canadian model digester for treating swine waste. In the anaerobic digestion process, batch reactors were used on a laboratory scale with a total volume of approximately 4 L and a working volume of 3.2 L. Three treatments were conducted to compare the efficiency of solid removal, the chemical oxygen demand (COD), and the production of biogas. The first treatment contained only swine waste; the second included the addition of glycerol at 1, 3, and 5% (w/v); and the third treatment included the addition of 1, 3, and 5% (w/v) of PBM residue in relation to the swine wastewater. From the results, it can be concluded that higher yields were obtained for the treatment with 3% PBM and 1% glycerol. Most treatments showed high removal rates of total solids and total volatile solids. Reductions lower than 70% were obtained only for treatments with PBM and glycerol at a ratio of 5%.